Integration between RCA and CE techniques and its role in reducing production costs -with applying to the textile industries in Iraq (Entrepreneurship Journal for Finance and Business, 2022)
This study aimed to demonstrate the role of the integration of RCA and CE technologies in reducing production costs in Iraqi industrial companies, through the application to the data of the fiscal year (2020) for the Nasiriyah textile factory affiliated to the General Company for Woolen Industries, and the study showed several results from The most important of them :- There is a possibility to apply the techniques of RCA and CE in the Iraqi industrial companies.-The integration between the two techniques of accounting for resource consumption and simultaneous engineering leads to the optimal exploitation of idle energy and work to exploit it through the work of restructuring some of the things in the activities of the factory.- Also, this integration enables the company's management to discover idle energy and exploit it and delete activities that do not add value to the product.- The company's customers in general do not prefer the mat to enter furniture that matches the mat in quality and price.The researchers presented a number of suggestions in the light of these conclusions that could contribute to developing the competitive advantage of companies operating in the textile industries sector in Iraq.